Implementation of a preventive maintenance system, based on augmented reality - Hamidane Rabie (PAIS'2018 3rd International Conference on Pattern Analysis and Intelligent Systems 7-28 Octobre, Universite de Tebessa, 2018)
In this article, we present ARPM (Augmented Reality-based Preventive Maintenance) system, which aims at offering to the technician of a Cement Factory a virtual assistance in real time using various forms of 3D models, images or even texts, in order to help him to maintain and inspect his equipment. This system not only offers the possibility of reducing costs of the preventive maintenance, but also allows monitoring and even anticipating failures. In order to ensure a reliable maintenance operation, we adapted our system to be compatible with the CMMS system (Computerized Maintenance Management System) already exists in the Cement factory